PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP KEPEMIMPINAN PRESIDEN JOKO WIDODO - Zahra Mufidah; Hambali, Hambali; Arianto, Jumili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to state and analyze the nature and type of leadership of President Joko Widodo based on the perceptions of Riau University students. The method in this research is quantitative descriptive, the primary data collection instruments used in this research are questionnaires or commonly called questionnaires and interviews which consist of 2 indicators, each of which has 5 and 10 sub-indicators with 40 statements. The population in this study were Riau University students. Sampling from the entire population used the Quota Sampling technique, so that the researchers gave a quota of 10 people in 10 faculties at Riau University. Based on the research results, it was found that the average percentage value of respondents’ alternative answers was 62.2%, this percentage was in the “Good” category with a range of 50.01%-75,00%. Thus, it can be concluded that the overall results of research on Riau University Students’ Perceptions of President Joko Widodo’s Leadership are in the “Good” category.